TECHNICAL EFFICIENCY OF SHRIMP FARMING IN COASTAL MAHARASHTRA: A PRODUCTION FUNCTION APPROACH - Sadafule, Nakul, A.; Salim, Shyam, S.; Pandey, S. K.; Debnath, Biswajit (Journal of Indian Fisheries Association, 2014)
Among the different shrimp species cultured in India Tiger Shrimp, Peneaus mondon is the most  popular and commands considerable demand all over India including Maharashtra. In India, about 1.2 million hectares of potential area is suitable for shrimp farming. It has estimated that about 1.45 lakh tones of shrimp were produced during the year 2006. Shrimp farming has helped to increase the employment due to increase in production, transport, processing, marketing and export trade. However, the industry suffered various shocks including white spot disease, price fluctuation at international level and threat of antidumping by USA which resulted in increased risk in production and marketing, all these issues have direct bearing on the profitability and economics of shrimp farming operations. The present study on the technical efficiency of shrimp farming in the costal Maharashtra comprised of analyzing the status of the shrimp farming in the costal districts of Maharashtra, viz., Thane, Raigad, Ratnagiri and sindhudurg. The data on the shrimp farming was collected form a total sample size of 110 farmers using a pretested  questionnaire. The technical efficiency was estimated using Cobb Douglas production function. The results revealed that the water spread area, stocking density per hectare, fertilizer used and stocking density were the most important factors for determining the production of shrimp in all over Maharashtra. The cost of seed, quantity of feed and culture period were the most pertinent factors for determining the production of shrimp in Thane district. The culture period and quantity of feed were the most important factors for determining the production of shrimp in Raigad district. Stocking density, medicines cost and feed required were the most important factors for determining the production of shrimp in Ratnagiri and Sindhudurg districts. The study suggested the need for the concerted efforts in developing a disease management plan and evolving a viable marketing strategy for augmenting the production and higher unit value realization for the shrimp production. Key words: Technical efficiency, shrimp farming, coastal Maharashtra.